PEMANFAATAN APLIKASI DESKTOP PEMINJAMAN ALAT LAB PADA IKEST MUHAMMADIYAH PALEMBANG - Paray Theo Lonando; Arif Fadillah (IKesT Muhammadiyah Palembang, 2023)
Utilization of information technology in all fields is a must to assist operational activities in processing data quickly and precisely. Each IKesT Muhammadiyah Palembang health laboratory has assets in the form of goods or equipment to support practicum activities and the learning process of the laboratory system. In every semester of lectures there will be practicum activities for several subjects and will always involve laboratory assistants to prepare and teach practicum. where the borrowing process is still manual. Application is a subclass of computer software that directly utilizes computer capabilities to perform a task desired by the user. the author will build a system for borrowing goods and equipment at the Muhammadiyah Palembang IKesT laboratory Management Unit using a Desktop application using Laravel 8